KAJIAN AESTHETIK DAN SIMBOLIK PADA ELEMEN DEKORATIF KARAWO GORONTALO - Apsari Dj Hasan (Universitas Komputer Indonesia, 2019)
This study aims to examine the decorative types of Gorontalo karawo fabrics in aesthetic and symbolic elements. Researchers want to know as made in the research design, aspects that are present in the decoration of fabrics in aesthetic and symbolic elements. This study uses a number of related theories to get results, and as a determinant, the authors use aesthetic theory, as well as historical approaches. With this theoretical basis, the author seeks to describe the aesthetic aspects and symbolic meanings that exist in Gorontalo karawo fabric. Through the data collection of the chosen motif and provide a classification of motives, the part is used as a reference for research material. The results showed that Gorontalo filigree had an aesthetic value consisting of unity formed from the overall decorative motifs displayed, complexity formed by complexity in the manufacturing process, and intensity of seriousness in the manufacturing process or the impression displayed on the filigree motif. The aesthetic form also reflects the diversity of meanings for communication, such as the symbol of a leader with his noble instincts, a symbol of cultural cooperation, which is worth maintaining, and ideas about nature conservation. This research proves that the decoration in Gorontalo filigree cloth (karawo) does not only act as a visual value, but also as a communication of cultural meanings and social status. Of all these distinctive motifs show a relationship between humans and humans and humans with nature. The influence of culture from the Philippines is also known to have a strong influence on the emergence of the Gorontalo filigree namely manila filigree.